Potential Association Between Microsatellite Markers on Chicken Chromosomes 6, 7 and 8 and Body Weight - Campos, R.L.R.; Ambo, M.; Rosario, M.F.; Moura, A.S.A.M.T.; Boschiero, C.; Nones, K.; Ledur, M.C.; Coutinho, L.L. (International Journal of Poultry Science, 2009)
Selective Genotyping (SG) is a strategy used to reduce the total number of markers and animals to be genotyped in order to detect QTL in a large designed population. The objective of this study was to detect potential associations between microsatellite markers on chromosomes 6, 7 and 8 (GGA6, GGA7 and GGA8) and Body Weight at 42 days (BW42), using an F2 population developed by crossing a broiler (TT) and a layer (CC) lines. Chickens were separated by sex and BW42 of 2,063 F2 offsprings was adjusted for the hatch effect. Animals that presented extreme phenotypes, i.e. the 4.5% lightest and heaviest from the normal distribution curve of phenotypes were selected within dam families, comprising 170 chickens. The means and standard deviations from the lightest and heaviest groups were 801.5 ±93.8 g and 1,328.5 ±127.8 g, respectively. Fourteen parents (TT males and CC females) and the selected 170 F2 chickens were genotyped with 25 microsatellite markers, seven on GGA6, 11 on GGA7 and seven on GGA8. Statistical analyses used the chi-square (p